Letter to the Editor 33(4) - Yasmin, Rubina; Hossain, Syeda Fahmida (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2015; 33(4): 235-236